Effects of Dietary Protein Levels on Digestion, Metabolism, Serum Biochemical Indexes, and Rumen Microflora of Lanzhou Fat-Tailed Sheep - Na Jiao; Wangmei Feng; Chi Ma; Honghe Li; Junsong Zhang; Juanshan Zheng; Penghui Guo (Animals)
This study aimed to investigate the effect of varying levels of dietary protein on digestion, metabolism, serum biochemical indexes, and rumen microflora in Lanzhou fat-tailed sheep. A total of twenty 8-month-old healthy rams with an initial average body weight (BW 25.16 ± 1.09 kg) were selected and randomly divided into four dietary treatments with different protein levels P: 9.47%, MP: 10.53%, HP: 11.56%, and EHP: 12.61%. The rams underwent a 23 day adaptation period, and the experiment was conducted for 7 d. The results showed that with increased dietary protein levels, the apparent digestibility of dry matter (DM), crude protein (CP), acid detergent fiber (ADF), and urine energy significantly increased (p < 0.05), increasing by 8.65%, 7.31%, 6.22%, and 0.1%, respectively. In contrast, the digestibility of neutral detergent fiber (NDF) first increased and then plateaued with the increase in protein levels, and the digestibility of NDF in the HP group was the highest (p < 0.05). The Shannon, Simpson, Chao1, and Ace indices of rumen microorganisms in the four groups did not change significantly (p > 0.05). Additionally, at the phylum level, the relative abundance of Bacteroidota, Firmicutes, and Verrucomicrobiota collectively accounted for over 91% of the total phylum composition. At the genus level, there was an increase in the relative abundance of uncultured_rumen_bacterium and Rikenellaceae_RC9_gut_group in the LP group, whereas the relative abundance of Prevotella decreased. In comparison to the other three groups, the HP group exhibited an increase in the relative abundance of Firmicutes. In summary, dietary protein level had no significant effects on the rumen microflora structure and blood biochemical indexes. However, diets with a high protein level can improve the apparent digestibility of nutrients and energy use efficiency of Lanzhou fat-tailed sheep.